Investigating the distribution of heat transfer in a thick-walled functionally graded cylindrical shell under heat flux - Buqing Zhang; Zhiqiang Long; Guoqing Liu; Zhengxin Wu; Qiang Yan (Journal of Engineering and Applied Science)
Abstract The primary aim of this work is to investigate the heat transfer behavior in a thick-walled functionally graded cylindrical shell subjected to internal pressure and thermal gradients, specifically focusing on how different material grading profiles (linear, exponential, and power-law) affect thermal performance. This study examines the influence of material gradation on the temperature distribution by considering variations in Young’s modulus, thermal conductivity, expansion coefficient, and yield stress as functions of the shell’s radial position, based on the Erdogan model. Finite element analysis (FEA) utilizing ABAQUS software was used to conduct the steady-state and transient heat transport calculations in an aluminum metal/alumina ceramic shell. For a pure aluminum shell, it is about 15% of the temperature difference between the inner and outer surfaces for the inner temperature of 115 °C and the outer one of 136 °C. By contrast, the ceramic shell thermal insulation reduces the outer wall temperature by 85%: the inner surface temperature is 149 °C and the outer surface 28 °C. Besides, the analysis of several grading profiles evidenced that quite different heat transfer features occur across the component: more steep temperature gradients and higher thermal insulation result when exponential grading is used instead of a linear one. These findings highlight the role of FGM and the optimization of grading profiles in improving high-temperature thermal management applications.